2014
DOI: 10.1136/jclinpath-2013-202163
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of integrin αv correlates with poor prognosis in colorectal cancer

Abstract: Overexpression of integrin αv is associated with advanced T and N stage and as an independent prognostic factor in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Subsequently, we examined the correlation of individual cell migration-associated genes such as integrins ( ITGA and ITGB ), cell adhesion molecules (E-selectin, VCAM1 and ICAM1 ), neuropilins ( NRP1 and NRP2 ) and epithelial-to-mesenchymal transition transcription factors ( ZEB1 and ZEB2 ), with AXL , MERTK and TYRO3 (Fig 2 and S3 Fig). Some of these genes, such as ITGA5 , E-selectin ( SELE ), VCAM1 , ICAM1 , NRP1 and NRP2 have previously been implicated in CRC progression [4145]. These genes associated strongly with AXL .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we examined the correlation of individual cell migration-associated genes such as integrins ( ITGA and ITGB ), cell adhesion molecules (E-selectin, VCAM1 and ICAM1 ), neuropilins ( NRP1 and NRP2 ) and epithelial-to-mesenchymal transition transcription factors ( ZEB1 and ZEB2 ), with AXL , MERTK and TYRO3 (Fig 2 and S3 Fig). Some of these genes, such as ITGA5 , E-selectin ( SELE ), VCAM1 , ICAM1 , NRP1 and NRP2 have previously been implicated in CRC progression [4145]. These genes associated strongly with AXL .…”
Section: Resultsmentioning
confidence: 99%
“…The tissues of non-small cell lung cancer were observed abnormal elevation of integrin αV expression that was believed to promote tumor proliferation and progression [23]. Overexpression of integrin αV correlates well with the shorter survival of patients with colorectal cancer [24]. Integrin αVβ3 mediates the interaction with extracellular matrix as an adhesion molecule, but overexpressed integrin αVβ3 initiates endothelial cell survival in anchorage independence and tumor metastasis without ECM ligand binding [5].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Nakada et al [23] reported that ITGα3 is over-expressed in glioma stem-like cells and promotes invasion. Furthermore, evidence shows that overexpression of ITGαv is closely associated with the metastasis and progression of some cancers [24, 25]. …”
Section: Discussionmentioning
confidence: 99%